Enjoyment and the Other in the Psychoanalytical Theory of Jacques Lacan - Pocius, Kasparas (Sociologija. Mintis ir veiksmas, 2020)
This article analyses the concept of enjoyment, proposed by Jacques Lacan, the French theoretician of psychoanalysis. The aim is to show the relation between the enjoyment and the other and to find a possibility to create different social relations in which the other (an individual or a group) is not an obstacle for individual or collective enjoyment but its foundation. In this article I develop the Lacanian argument of enjoyment how a plane of the Real, the possibility to meet the other as a person in everyday situations, allows an individual to maintain solidarity with that other person which before was his imaginary competitor.